Draft Annual Plan 2010-11 Volume - II Government of Karnataka - Planning Commission (Planning Commission, 2010)
Draft Annual Plan 2010-11 Proposed Outlays Draft Annual Plan 2010-11 Proposed Outlays - Scheme wise allocation Physical Targets and Achievements Statement Regarding External Aided Projects Bharath Nirman Programmes, Centrally Sponsored Scheme Draft Annual Plan 2010-11- Financial Outlays proposals for TSP Draft Annual Plan 20010-11 Physical Targets and achievements proposals for TSP Draft Annual Plan 2010-11 - Financial Outlays proposals for SCSP Draft Annual Plan 2010-11 Physical Targets and achievements proposals for SCSP.
Government of Karnataka, Planning, Programme Monitoring and Statistics Department